Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT Stars Internasional Surabaya (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2022)
This research is aimed to examine the effect of communication and work environment on employee performance. This research was carried out at the PT Stars International, Surabaya office with quantitative method and collect data by questioner, interview, observation. Population research is all permanent employee at the PT Stras International, Surabaya office with a large sample taken as many as 33 samples and analysis data use SPSS program version 25. The data analysis technique used in this study is multiple linear regression test, determination coefficient test, and hypothesis test. Based on the result of research and hypothesis test that has been done shows there is a significant influence of communication and work environment effect the employee performance at the PT Stars International, Surabaya together (simultaneous) this can be seen from the value of F arithmetic greater than F table is 9,791 greater than 3,3158. Hypothesis test results partially communication on employee performance shows a significant effect this can be seen from the t value is greater than t table is 2,763 greater than 2,0423. Hypothesis test results partially work environment on employee performance shows a significant effect this can be seen from the t value is greater than t table is 2,103 greater than 2,0423. For the results of hypothesis testing the coefficient of determination (R square) in this study shows that the communication and work environment variables have an influence of 39.5% on employee performance.